Options and Requirements. A Study of the External Process of Specialized Document Production - Van Vaerenbergh, Leona; Schubert, Klaus (HERMES - Journal of Language and Communication in Business, 2010)
The process of producing a specialized document can be considered to consist of an internal and an external part. The internal process is the mental or cognitive side, not accessible to direct observation, whilst the external process is all which can be witnessed by an observer. We model the internal part as a process of decision-making which is steered by controlling inﬂuences. These originate in the external process. The way in which the task, the agents and the controlling inﬂuences interrelate is then elaborated on in an empirical analysis of the production process of Patient Information Leaﬂets.